ANTI-MONEY LAUNDERING CRIMES IN ISLAMIC LAW COMPARED TO THE ALGERIAN AND INDONESIAN LAW - Driss, Bakhouya (Jurisdictie: Jurnal Hukum dan Syariah, 2016)
Islamic law agreed with most modern laws on the seriousness of money laundering crimes, including Algerian law and Indonesia, despite the differences in regard to the methods which these crimes because of the different banking systems from one country to another on the one hand, because of the possibilities available to money launderers on the other.      This led to the need to pay special attention by the Algerian law and Indonesia in order to effectively provide for these modern criminal phenomena, it has resorted to the imposition of strict controls to combat the phenomenon is mostly derived from the provisions of Islamic Sharia.      Although the procedures and mechanisms that came in the Islamic Sharia and stipulated in the fight against money laundering in Algeria, Indonesia law, but many obstacles stand in the way without effective control of this crime along the lines of the principle of banking secrecy, which is an obstacle, often without disclosure of relevant financial transactions money laundering offenses.